Greece : a short history of a long story, 7,000 BCE to the present - Thomas, Carol G., 1938- (Chichester, West Sussex, UK : John Wiley and Sons, Inc., 2014)
"Greece : A Short History of a Long Story presents a comprehensive overview of the history of Greece by exploring the continuity of Greek culture from its Neolithic origins to the modern era. Tells the story of Greece through individual personalities that inhabited various periods in the lengthy sweep of Greek history. Uses an approach based on recent research that includes DNA analysis and analyses of archaeological materials. Explores ways in which the nature of Greek culture was continually reshaped over time. Features illustrations that portray the people of different eras in Greek history along with maps that demonstrate the physical sphere of Greece and major events in each of the periods"--
Mountains and Sea -- The Age of Heroes -- End of the Bronze Age : Slow Reshaping -- The Second Age of Heroes : Classical Greece -- Incorporation into a Larger State -- Graecia Capta : Roman Control -- Power Returns to Greece : The Byzantine Empire -- Ottoman Greece, 1453-1821 -- Building a New State, 1821-1935 -- A Player in the Modern World : 1935-Present.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: HISTORY / Europe / Greece (see also Ancient / Greece).; Civilization; Greece -- History; Greece -- Civilization; Greece; Electronic books; History